From Power and Privilege to Dignity and Respect: Developing a Theory of Species Stratification and Interspecies Dominance - Blount-Hill, Kwan-Lamar; Oder, Paul (Frontiers in Ecology and Evolution, 2020)
Traditional conservation scientists approach conservation conflict from a resource-management perspective, in which both wildlife and non-living natural resources are managed to balance the interests of competing human stakeholders. We instead consider conflict between the powerful and less powerful humans and wildlife alike. Applying tenets of social dominance theory to ecological networks, we propose that socio-political power structures that marginalize human populations – denying voice and inclusion – may align with similar neglect of wildlife species. Considering nonhuman species as collections of agentic beings seeking to satisfy their own survival interests and that of their respective "social" group, we connect the subjects of social justice and ecological justice through common challenges rooted in the social psychology of power.